Employment Booms and Busts Stemming from Nonrenewable Resource Extraction - Jeffords, Chris; Thompson, Alexi; Yerger, David (International Journal of Energy Economics and Policy, 2015)
A nonrenewable resource extraction model is embedded within a lake model of industry-specific employment, where flows to (from) employment from (to) unemployment depend on the attachment (separation) rate. The attachment and separation rates vary with resource extraction, and the results, driven by the rate of extraction and the remaining resource stock, indicate that changes in the stationary employment level can be positive, negative, or zero. There is a range where the separation rate is decreasing (increasing) and the attachment rate is increasing (decreasing), and the change in employment is determined by the combined effect of these changes. Using data on coal production and employment in the U.S. as a guide, simple calculations provide a range of years beyond 2013 when it is expected that peak employment will be reached in the Marcellus Shale, and the results suggest that employment gains will likely continue for at least a decade. Keywords: Marcellus Shale; Shale gas; Nonrenewable resource; Employment; Lake model JEL Classifications: Q32; Q33; Q47